Cardiovascular outcomes of antidiabetic drugs - Nath, Ranjit Kumar; Pandit, Neeraj; Raj, Ajay; Pandit, B.N; Kumar, Vinod; Bhardwaj, Rajeev; Singh, Ajay Pratap; Thakur, Ashok (Asian Journal of Medical Sciences, 2021)
Type 2 Diabetes Mellitus (T2DM) is associated with a high risk of atherosclerotic cardiovascular disease (ASCVD). Intensive blood glucose reduction with antidiabetic drugs significantly reduce microvascular complications but there is no strong evidence of reduction in cardiovascular (CV) events. In 2008, the US Food and Drug Administration (FDA) issued guidance to demonstrate cardiovascular safety of newer antidiabetic drugs in addition to reduction in blood glucose level. After which a number of CVOTs were conducted involving newer antidiabetic drugs. The newer drugs (e.g. GLP-1 RAs, SGLT2 inhibitors and DPP 4 inhibitors) might have potential effects on body weight, lipid parameters and blood pressure, as well as endothelial dysfunctions, inflammatory markers and oxidative stress. The current review summarizes the results of the main trials focused on the cardiovascular outcomes of traditional as well as newer antidiabetic drugs.